Pancreatic changes related to aids in children - Daher, João Paulo L.; Xavier, Analúcia R.; Cardoso, Lucilene C.; Kanaan, Salim; Lopes, Vânia Glória S.; Silva e Carvalho, Licínio E. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: recent studies have revealed the existence of serious pancreatic manifestations in the terminal stages of HIV infection. Few reports are found to correlate, in terms of anatomic pathology, HIV infections, etiologic agents of opportunistic infections and drugs used in different treatments. Objective: this study aims to establish the correlation between children with AIDS, its treatment and the frequency of opportunistic infections with the occurrence of pancreatitis. Methods: data of 14 pediatric autopsies (seven females and seven males, aged 3 months to 11 years old) with clinical and laboratory diagnosis of AIDS have been correlated. Autopsies were performed at the Department of Pathology, HUAP, Fluminense Federal University. Results: the results showed macroscopic changes in three cases and microscopic changes compatible with pancreatitis, in seven cases. Out of 14 patients, three were using antirretroviral medication and 12 had opportunistic infections, two of them with more than one infectious agent. Conclusion: our findings reinforce the positive correlation between HIV and pancreatitis, suggesting that common opportunistic infections may be related to the etiology of pancreatitis detected in these patients. The pancreatic involvement does not appear to be related to the antirretroviral usage. This study will provide subsidies for understanding the pathogenesis of pancreatic involvement caused by HIV virus, opportunistic agents and drugs used in therapy.